Carboxylic acid production from ensiled crops in anaerobic solid‐state fermentation ‐ trace elements as pH controlling agents support microbial chain elongation with lactic acid. Issue 7 (14th May 2018) - Sträuber, Heike; Bühligen, Franziska; Kleinsteuber, Sabine; Dittrich‐Zechendorf, Michael
Abstract: Background: For the production of carboxylic acid platform chemicals like medium‐chain fatty acids (MCFA) by anaerobic fermentation, pH control is required. However, adding buffer solutions is ineffective in leach‐bed reactors. Aim: In order to increase the MCFA production by maize silage fermentation and to engineer the process we investigated the effect of solid alkaline iron and manganese additives on the process performance and microbial community dynamics. Results: Without additives, the pH dropped to 3.9 and lactic acid bacteria were favored. Total product yields of 207 ± 5.4 g organic acids (C2 ‐C6 ) and alcohols per kg volatile solids were reached. The addition of trace elements increased the pH value and the product spectrum and yields changed. With a commercial iron additive, the product yields were higher (293 ± 15.2 g/kgvolatile solids ) and supposedly clostridia used lactic acid for microbial chain elongation of acetic acid producing n ‐butyric acid. With the addition of pure Fe(OH)3 or Mn(OH)2, the total product yields were lower than in the other reactors. However, increased production of MCFA and the occurrence of distinct bacterial taxa ( Lachnospiraceae, Ruminococcaceae and Megasphaera ) related to this metabolic function were observed.Conclusions: The application of alkaline trace metal additives as pH stabilizing agents can mitigate spatial metabolic heterogeneities when trace metal deficient substrates like specific crops or residues thereof are applied.